The correlation between serum levels of laminin, type IV collagen, type III procollagen N-terminal peptide and hyaluronic acid with the progression of post-COVID-19 pulmonary fibrosis - Yu, Dapeng; Yin, Guangyue; Lei, Jing; Gong, Yijun; Zheng, Liang; He, Dahui; Lei, Lihua; Sun, Lei (Frontiers in Cell and Developmental Biology, 2024)
COVID-19 patients often suffer from post-COVID-19 acute sequelae (PASC). Pulmonary fibrosis (PF) has the most significant long-term impact on the respiratory health of patients, known as post-COVID-19 pulmonary fibrosis (PC19-PF). PC19-PF can be caused by acute respiratory distress syndrome (ARDS) or COVID-19-induced pneumonia. Individuals who experience COVID-19 pneumonia symptoms (including cough, shortness of breath, dyspnea on exertion, and desaturation) for at least 12 weeks after diagnosis, almost all develop PC19-PF. Extracellular matrix molecules: laminin (LN), type IV collagen (IV Col), procollagen III Nterminal peptide (PIIINP), and hyaluronic acid (HA) are involved in the development and progression of PC19-PF. This study aimed to investigate the relationship between the progression of PC19-PF and serum levels of LN, IV COL, PIIINP, and HA. This retrospective study included 162 PC19-PF patients treated and 160 healthy controls who received treatment at